A Systematic Review on Image Data Protection Methods - Faraj Ali Alyaqobi; Nor Adnan Bin Yahaya (International Journal of Informatics and Information Systems, 2022)
Securing data is the main goal of any data security system (DSS). Valuable data must be protected all the time and stored in a very highly secure data storage device. This need has become more critical due to the continuous growth of data size. Furthermore, non-text data in the form of images, audio, and videos can now be transferred and processed easily and thus become part of sensitive data that needs to be protected. Since there is a need to secure and protect data in any form in order to keep them private and valid, it is expected that there would be many attempts already that have been proposed in the literature for this purpose. This paper reviews a group of these proposed strategies and methods that have been applied to different kinds of DSSs. Challenges and future trends of DSSs are also discussed. A number of main findings are grouped and organized as follows: (1) there are many different kinds of security techniques, each of which offers varying degrees of performance in terms of the amount of data and information that can be managed securely, (2) depending on the architecture of the proposed method, the tactics or strategies of the security system, the kinds of DSSs, as well as a few other factors, some methods are more appropriate for the storage of certain categories of data than others.